10 - Gendered Epidemics and Systems of Power in Africa: A Feminist Perspective on Public Health Governance - Marindo, Ravayi (Africa Development, 2017)
This article is about systems of power, and the way different power systems – global, local, patriarchal and family – interconnect and create vulnerability to epidemic and infectious diseases among those with less power, mostly poor, resource-limited rural African women. The main argument is that to understand gendered epidemics in Africa, we need to examine the systems of power that create and perpetuate African women’s vulnerabilities at local, national and global levels. The article uses case studies, extracted from published epidemic stories and interprets these cases from a feminist and power analytical framework. The results suggest that while a disease or an epidemic affect a group of individuals, systemic factors regarding responsible governance and the role of national politics and policies; the role of global systems that control knowledge production and sharing; as well as patriarchy and culture all contribute to creating an environment that increases women’s vulnerability to epidemics.The article concludes by advocating for strengthening practical ways that can make hierarchical power less attractive and equitable distribution of power more attractive. Since current systems of power cannot be eliminated, they need to be challenged and transformed. The article has various limitations. It relies on a small number of case studies and though the literature refers to gender, the analysis is predominantly of women. Notwithstanding these limitations however, the article aims to contribute to the ongoing scholarly debate on governance of public health in Africa as well as to the growing field of African feminist epidemiology.